Psychological and medical advantages of breastfeeding; the role of psychological consultations for women after birth - Okoniewska, Ewelina; Gwiazdowska-Stańczak, Sylwia; Dobrowolska, Monika (Medical Studies/Studia Medyczne, 2021)
Human milk is the best food for newborns. A lot of doctors and specialists connected with obstetrics devote themselves to informing and encouraging women to breastfeed; however, there are still problems with deciding on such a way of feeding the infant. Some women still have little knowledge about the medical and psychological advantages of breastfeeding for the newborn and herself. The article discusses the advantages of breastfeeding and the psychological problems that may block women from deciding on such a way of breastfeeding. Among the most common barriers are social pressure, a rapid desire to return to work and the anxiety associated with it, stress, postpartum depression, and lack of knowledge about the advantages of human milk. It is very important to take up this subject because often women do not breastfeed because of psychological rather than medical problems. In such a situation it is worth recommending, as well as diagnostic tests and lactation advice, also psychological consultation.